ANALISIS PENGARUH FAKTOR-FAKTOR DEMOGRAFI TERHADAP KEPATUHAN PERPAJAKAN - Sri Mulyani; Nita Andriyani Budiman; Riyadlus Mei Sakinah (Jurnal Dinamika Ekonomi & Bisnis, 2020)
This study aims to determine how the influence of demographic factors on tax compliance. The data collection is done by distributing questionnaires and the sample size of 100 respondents. This research was done KPP Pratama Kudus. Data were analyzed using Chi-Square test. Demographic factors examined included gender, age, education level, marital status, occupation, and income levels. The results showed that the respondent men and women have the same tax compliance while for age, education level, occupation, and income levels have different levels of tax compliance.